2020
DOI: 10.3390/hydrology7020036
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Actual Evapotranspiration Using the Remote Sensing Method and SEBAL Algorithm: A Case Study in Ein Khosh Plain, Iran

Abstract: The aim of this study was to estimate evapotranspiration (ET) using remote sensing and the Surface Energy Balance Algorithm for Land (SEBAL) in the Ilam province, Iran. Landsat 8 satellite images were used to calculate ET during the cultivation and harvesting of wheat crops. The evaluation using SEBAL, along with the FAO-Penman–Monteith method, showed that SEBAL has a sufficient accuracy for estimating ET. The values of the Root Mean Square Error (RMSE), Mean Absolute Percentage Error (MAPE), Mean Bias Error (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…also reported a range of ET from 348 to 385 mm under arid areas of Afghanistan Ghaderi et al (2020). reported the greatest and least amount of water required were 231 and 19.47 mm/hr, respectively.The amounts of evaporation, transpiration and evapotranspiration for I 2 treatment were also reduced by3, 18 and 14%, respectively, in 2006-2007 growing season and by 13, 8 and 9%, respectively, in 2007-2008 growing season.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…also reported a range of ET from 348 to 385 mm under arid areas of Afghanistan Ghaderi et al (2020). reported the greatest and least amount of water required were 231 and 19.47 mm/hr, respectively.The amounts of evaporation, transpiration and evapotranspiration for I 2 treatment were also reduced by3, 18 and 14%, respectively, in 2006-2007 growing season and by 13, 8 and 9%, respectively, in 2007-2008 growing season.…”
mentioning
confidence: 90%
“…Wheat is considered as a moderate water user crop, but in arid and semi-arid regions its water requirements can be substantial, requiring practicing effective water management strategies. On a global scale, water withdrawal for agricultural purposes accounts for about 75-80% of all water withdrawals and the Food and Agriculture Organization of the United Nations (FAO) has predicted a 14% net increase in water use to meet the food demands by the year 2030 as compared with year 2000 (FAO 2008). To meet this increasing demand for food by rapidly growing world's population, effective irrigation management strategies need to be deployed to enhance water productivity (WP) of major commodity crops.…”
Section: Introductionmentioning
confidence: 99%
“…The model shows good efficiency for estimating the actual ET of the pistachio product [25]. Moreover, SEBAL was used to calculate ET during the cultivation and harvesting of wheat crops in the Ilam province, Iran [26]. Thus the evaluation using SEBAL and the FAO-Penman-Monteith method showed that SEBAL has sufficient accuracy for estimating ET.…”
Section: Using Of Sebal Model For Et Estimationmentioning
confidence: 99%
“…A linear correlation and the root mean square error (RMSE) between the measured (FAO P-M) and the SEBAL daily ETa was computed [13]. The RMSE was calculated as follows [26]:…”
Section: Validation Of the Sebal Model Evapotranspirationmentioning
confidence: 99%
“…In the above equations, M Exp is laboratory data, M Cal is calculated data from extractive equations, N is the number of data, σ M Exp and σ M Cal are the sum of laboratory and computational data, M Exp and M Cal are the average of laboratory and computational data, respectively. It should be noted that the best solution is when the RMSE coefficient is zero, and the R 2 coefficient is one [36]. The quality range of the KGE coefficient is as follows.…”
Section: Specific Energy Equations and Evaluation Criteriamentioning
confidence: 99%